Epidemiology of the initial period of novel coronavirus (COVID-19) pandemic in the Republic of Moldova - Nicolae FURTUNA; Alina DRUC; Octavian SAJIN; Constantin SPINU; Veaceslav GUTU; Alexei CEBAN (One Health & Risk Management, 2020)
Introduction. In the Republic of Moldova, the first case of COVID-19 was confirmed on March 7, followed by a significantly increasing incidence across the country. It is important to describe the clinical and epidemiological aspects that were adjusted to the national context in order to develop and implement optimal public health care measures. Material and methods. A cross-sectional descriptive study was conducted from March 7 to April 6, 2020, using the surveillance system data of the Republic of Moldova on COVID-19 case incidence. All cases of COVID-19 were confirmed by Real-Time PCR. Results. During the reference period, 965 cases of COVID-19 were registered, whereas the urban incidence rate was 1.4 times higher than the rural one. The mean age of infected population was 45.2 years, whereas the most affected age group was 50-59 years, found in 232 cases. Healthcare workers made up 26.6±1.4% out of 965 diseased patients. They included nurses – 34.2±3.0%, auxiliary medical staff – 29.6±2.8%, doctors – 27.2±2.8%, first-aid assistants – 7.4±1.6%, pharmacists – 1.2±0.7%, paramedics –0.4±0.4%. The health status of people diagnosed with COVID-19 was severe in 8.0 ± 0.9% of cases; moderate severity – in 34.7±1.5% and satisfactorily severe – in 57.3±1.6% of cases. Conclusions. The identified clinical and epidemiological aspects allowed readjusting the public health policies in order to prevent the spread of COVID-19 infection among the elderly and medical workers.